1990
DOI: 10.1080/10407789008944795
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Conduction-Convection Heat Transfer Model for the Valve Flow-Field Region of Four-Stroke Piston Engines

Abstract: A multidimensional method has been devised to solve the conjugate conduction-convection heat tmnsfer process at the sudace of a moving valve of finite thickness within the flow field of an opemh'ng four-stmke internal combustion (IC) engine. Heat exchange processes between the valve and the gases aajacent to these boundaries were also computed during the portions of the engine cycle when the valve was closed. Boundaries of the solution scheme were extended fired distances into the piston and cylinder liner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…that the above approach uncouples the gas phase from the solid phase. Similar engine heat transfer studies using simple geometry and physical models have also been reported in the past [9][10][11].…”
Section: Introductionsupporting
confidence: 60%
“…that the above approach uncouples the gas phase from the solid phase. Similar engine heat transfer studies using simple geometry and physical models have also been reported in the past [9][10][11].…”
Section: Introductionsupporting
confidence: 60%